Cognitive function is preserved in aged mice following long-term β-hydroxy β-methylbutyrate supplementation. (3rd March 2020) - Munroe, Michael; Mahmassani, Ziad S.; Dvoretskiy, Svyatoslav; Reid, Justin J.; Miller, Benjamin F.; Hamilton, Karyn; Rhodes, Justin S.; Boppart, Marni D.
Abstract : β-hydroxy β-methylbutyrate (HMB) is a nutritional supplement purported to enhance skeletal muscle mass and strength, as well as cognitive function in older adults. The purpose of this study was to determine the potential for long-term HMB supplementation to preserve muscle function and cognition in aged mice, as well as provide evidence of a link between vessel-associated pericyte function and outcomes. Four- (Adult/Ad) and 17 month-old (Aged/Ag) C57BL/6J mice consumed chow containing 600 mg/kg BW/day of either Ca-HMB (Ad, n =16; Ag, n =17) or Ca-Lactate (Ad, n =16; Ag, n =17) for 6 months. HMB did not prevent age-related reductions in muscle mass, strength and coordination (Age main effect, P <0.05). The rate of muscle protein synthesis decreased within the mitochondrial fraction (age main effect, P <0.05), and this decline was not prevented with HMB. Despite no change in muscle mass or function, an age-dependent reduction in active avoidance learning was attenuated with HMB (Age and HMB main effects, P <0.05). Age detrimentally impacted muscle-resident pericyte gene expression with no recovery observed with HMB, whereas no changes in brain-resident pericyte quantity or function were observed with age or HMB. The findings from this study suggest that prolonged HMB supplementation starting in adulthood may preserve cognition with age.